Conflict and diarrheal and related diseases: A global analysis - Bradley T. Kerridge; Maria R. Khan; Jürgen Rehm; Amir Sapkota (Springer, 2019)
The purpose of this study was to determine the association between deaths owing to terrorism, civil war and one-sided violence from 1994-2000 and disability-adjusted life years (DALYs) attributable to diarrheal and related diseases, schistosomiasis, trachoma and the nematode infections (DSTN diseases) in 2002 among World Health Organization Member States. Deaths resulting from terrorism, civil war and one-sided violence were significantly related to DSTN DALYs across the majority of sex-age subgroups of the populace, after controlling for baseline levels of improved water/sanitation and a variety of economic measures: overall, a 1.0% increase in deaths owing to terrorism and related violence was associated with an increase of 0.16% in DALYs lost to DSTN diseases. Associations were greatest among 0-to-4-year olds. The results of the present study suggest that DSTN disease control efforts should target conflict-affected populations with particular attention to young children who suffer disproportionately from DSTN diseases in these settings. In view of the evidence that terrorism and related violence may influence DSTN DALYs in the longer term, control strategies should move beyond immediate responses to decrease the incidence and severity of DSTN diseases to seek solutions through bolstering health systems infrastructure development among conflict-affected populations.